Usability of BLESS-implemented class room: a case study of mixtio - Desita Mustikaningrum; Astari Retnowardhani (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
Conventional learning system and e-learning have their own strengths and weaknesses. To combine both systems, blended learning is created. In Extention Program of Informatics Engineering Faculty at XYZ university most of the students already have jobs. As much 47.5 % of students who take this program have a job in daily office hours. Then, to facilitate the learning process the XYZ university develop learning management system (LMS) by Moodle. XYZ university want to make a learning process with blended learning concept. However, the Moodle sytem has limited function to adapt the blended learning system (BLS). In the aim to improve the class usability in BLS, then this study proposes to apply to Blended Learning System Structure (BLESS) into LMS design. BLESS is offered as a framework which matches to learning and uses a top-down approach. Then, the system design maed it “Mixtio”. At the end of this study, it can be seen the analysis result of the use of BLESS can improve system usability of LMS.